A "Push–Pull" Stabilized Phosphinidene Supported by a Phosphine‐Functionalized β‐Diketiminato Ligand. Issue 41 (6th July 2020) - Bestgen, Sebastian; Mehta, Meera; Johnstone, Timothy C.; Roesky, Peter W.; Goicoechea, Jose M.
Abstract: The use of a bis(diphenyl)phosphine functionalized β‐diketiminato ligand, [HC(CH3 )C2 ( ortho ‐[P(C6 H5 )2 ]2 C6 H4 )N2 ] − (PNac), as a support for germanium(II) and tin(II) chloride and phosphaketene compounds, is described. The conformational flexibility and hemilability of this unique ligand provide a versatile coordination environment that can accommodate the electronic needs of the ligated elements. For example, chloride abstraction from [(PNac)ECl] (E=Ge, Sn) affords the cationic germyliumylidene and stannyliumylidene species [(PNac)E] + in which the pendant phosphine arms associate more strongly with the Lewis acidic main group element centers, providing further electronic stabilization. In a similar fashion, chemical decarbonylation of the germanium phosphaketene [(PNac)Ge(PCO)] with tris(pentafluorophenyl)borane affords a "push–pull" stabilized phosphinidene in which one of the phosphine groups of the ligand backbone associates with the low valent phosphinidene center. Abstract : The synthesis and reactivity of a family of germanium(II) and tin(II) complexes supported by a bis(diphenyl)phosphine functionalized β‐diketiminato ligand is reported, including an intramolecularly stabilized "push–pull" phosphinidene.